2022
DOI: 10.3389/fimmu.2022.796349
|View full text |Cite
|
Sign up to set email alerts
|

Post-Transplantation Cyclophosphamide Uniquely Restrains Alloreactive CD4+ T-Cell Proliferation and Differentiation After Murine MHC-Haploidentical Hematopoietic Cell Transplantation

Abstract: Post-transplantation cyclophosphamide (PTCy) reduces the incidence and severity of graft-versus-host disease (GVHD), thereby improving the safety and accessibility of allogeneic hematopoietic cell transplantation (HCT). We have shown that PTCy works by inducing functional impairment and suppression of alloreactive T cells. We also have identified that reduced proliferation of alloreactive CD4+ T cells at day +7 and preferential recovery of CD4+CD25+Foxp3+ regulatory T cells (Tregs) at day +21 are potential bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 67 publications
2
11
1
Order By: Relevance
“…In their recent article Hadjis et al. investigated whether post-transplant cyclophosphamide (PT-CY) is unique in protecting against graft-versus-host disease (GvHD) by comparing it to multiple other “optimally dosed” chemotherapeutics ( 1 ). They concluded that PT-CY was superior to all other agents in ameliorating both clinical and histopathological GvHD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In their recent article Hadjis et al. investigated whether post-transplant cyclophosphamide (PT-CY) is unique in protecting against graft-versus-host disease (GvHD) by comparing it to multiple other “optimally dosed” chemotherapeutics ( 1 ). They concluded that PT-CY was superior to all other agents in ameliorating both clinical and histopathological GvHD.…”
mentioning
confidence: 99%
“…report, a B6C3F1/Crl (H-2 b/k ) → B6D2F1/Crl (H-2 b/d ) mouse model was used. Recipient mice were conditioned with 10.5 Gy of single dose total body irradiation (TBI), were given 10 7 bone marrow cells along with 4x10 7 splenocytes (SC) on the same day (day 0), and received levofloxacin in their drinking water ( 1 ). We used a CB6F1 (H-2 d/b ) → CAF1/J (H-2 d/a ) model with recipient mice conditioned on day -1 with 6 or 10 Gy of TBI and infused 10 7 donor bone marrow cells along with 3x10 7 SC without prophylactic antibiotics ( 2 ).…”
mentioning
confidence: 99%
“…39 The therapeutic efficacy of PTCy was previously attributed to the selective killing of alloreactive T cells that become activated and preferentially proliferate early post-HCT. 6 Although we have shown here and in prior studies that PTCy does broadly kill a substantial number of T cells, 6,7,14,16,17 this effect does not appear selective for alloreactive T cells. 6,14,16,17 Even so, the allure of the idea of cyclophosphamide selectively killing proliferating alloreactive T cells endures.…”
Section: Discussionmentioning
confidence: 46%
“…6 Although we have shown here and in prior studies that PTCy does broadly kill a substantial number of T cells, 6,7,14,16,17 this effect does not appear selective for alloreactive T cells. 6,14,16,17 Even so, the allure of the idea of cyclophosphamide selectively killing proliferating alloreactive T cells endures. We found that proliferating CD8 + T cells were reduced after PTCy but a sizable population remained, distinct from that seen with CsA or rapamycin treatment.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation